Program web-based SFBC untuk mereduksi kecemasan akademik siswa saat pandemi COVID-19; sebuah pilot studi - Kadek Suranata; Bimoe Bagus Prakoso (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
This research is a pilot study which aims to created the website and analyzed the effectiveness of a website-based solution focused-brief counseling (SFBC) program to reduce academic anxiety experienced by high school students. This study conducted by one group pretest-postest experimental design and involving 30 high school students in Singaraja, Bali as participants. The academic anxiety scale is used to measure the academic anxiety condition of students before attending counseling and also after. Student perception questionnaires were used to evaluate the feasibility of the program based on students' perceptions as users. Student academic anxiety data were analyzed through an independent sample t-test assisted by the JASP version 0.13 program. Data about the feasibility of web-based SFBC based on students' perceptions was analyzed descriptively and narrated. The results showed that: 1) the website-based SFBC program was effective in reducing academic anxiety experienced by high school students; 2) the website-based SFBC program has a good level of acceptance and feasibility based on the perceptions of students. The results of this study have implications for the use of website-based counseling methods for students.